Effect of vegetable seed oils on methane emission and fermentation of feed in vitro - MAHAJAN, CHETNA; MANGAL, KAJAL; WADHWA, M (The Indian Journal of Animal Sciences, 2016)
A study was conducted to assess the effect of carrot seed oil, canola seed oil and rape seed oil on rumen fermentation and methanogenesis in-vitro. The oils were supplemented to the complete feed (oat fodder and concentrate mixture in 60: 40 ratio) @ 1, 2 and 3% on DM basis, incubated for 24 h in 100 ml glass syringes. The digestibility of NDF varied significantly with highest in rapeseed and lowest in carrot seed, while OM digestibility and ME availability did not show any significant differences amongst the supplemented oils. The in-vitro methane production from complete feed supplemented with rape seed oil was observed to be the lowest. The TVFAs, acetate and propionate levels were highest in canola oil while A: P ratio was lowest. TVFA and acetate levels were highest at 1% level of supplementation, whereas propionate level was highest in control followed by at 1% supplementation. The methane production was significantly higher in oil supplemented groups as compared to control group, but amongst the oil supplemented groups it was significantly lowest when oil was supplemented at 3% level. Amongst the various oils evaluated for in vitro methane mitigation, the study conclusively revealed that the supplementation of diet with rape seed oil @ 2–3% on dry matter basis had an edge over other oils and levels.